Revivalisme Islam Versus Keadilan Gender - Triantini, Zusiana Elly (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
Gender as a subject itself has been around for quite some time in Indonesia, as has the fight for it by government and non-government organizations. Why is it then, that many victimized women still find themselves devoid of rights? Many contemporary views have cast the topic of gender equality as a virus to Indonesian women, especially Muslim women. So why does the fight for gender equality seem stagnant? It seems that for Indonesia, such a cause is mired in by many obstacles. The great wall of patriarchic culture and such defaming claims by 'Islamic' revivalist movements such as HTI, MMI or KPPSI have long lives indeed. Helped along by the comfortable armchair position of men, firmly entrenched in society and backed up by a headstrong dogmatic position on religious interpretation. Sadly, many women still nod to such a position, accepting it as one of the facts of life. Such phenomenon has driven the writer to realize that the struggle for gender equality is far from over. And that a mapping out and elaboration on the extent of challenges facing it would be most beneficial to those fighting for it. In hopes that it would help them in designing proper strategies to more effectively campaign for equality.